Factors Affecting the Implementation of School Health Programs for Elementary School - Darusman (Universitas Serambi Mekkah, 2021)
The purpose of this study was to know how the influence of knowledge, facilities, infrastructure and the role of teachers on the implementation of the School Health Program Program (UKS) in elementary schools in Simpang Kiri, Subulussalam City. This study includes survey research. Sources of data are all school principals and UKS totaling 30 people. The data collection technique is a questionnaire. Data were analyzed by univariate and bivariate analysis with chi-square test approach. The results showed that the implementation of the program had a close relationship with the knowledge of teachers, facilities and infrastructure and the role of teachers in each school. This means that the better the knowledge of teachers, facilities and infrastructure and the role of teachers in each school, the better the implementation of the school health program program (UKS) in that school. In the implementation of UKS in the Simpang Kiri working area, Subulussalam City, several parties involved in the UKS program have not implemented their roles and functions optimally, as well as the available facilities and infrastructure are not adequate so that the implementation of UKS has not functioned properly.